2013
DOI: 10.1002/anie.201308363
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Phosphonate Methyltransferase in the Identification of the Fosfazinomycin Biosynthetic Gene Cluster

Abstract: Natural product discovery has been boosted by genome mining approaches, but compound purification is often still challenging. We report an enzymatic strategy for “stable isotope labeling of phosphonates in extract” (SILPE) that facilitates their purification. We used the phosphonate methyltransferase DhpI involved in dehydrophos biosynthesis to methylate a variety of phosphonate natural products in crude spent medium with a mixture of labeled and unlabeled S‐adenosyl methionine. Mass‐guided fractionation then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 31 publications
0
58
0
1
Order By: Relevance
“…Putative ATP-grasp ligase and GCN5-related N-acetyltransferases (GNAT; FemXAB nonribosomal peptidyltransferase) encoded by neighboring genes may catalyze peptide bond formation. Similar enzymes are used in the biosynthesis of the phosphonopeptides rhizocticin (21) (ATP-grasp ligases) and dehydrophos (37) (GNAT), and a combination of both has been suggested to account for the peptide linkages in fosfazinomycin (38). Argolaphos has broad-spectrum antibacterial activity, with the highest efficacy against Salmonella typhimurium, Escherichia coli, and Staphylococcus aureus, and it is weakly inhibitory against Mycobacterium smegmatis (SI Appendix, Fig.…”
Section: Dereplication Of Phosphonate Biosynthetic Pathways and Produmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative ATP-grasp ligase and GCN5-related N-acetyltransferases (GNAT; FemXAB nonribosomal peptidyltransferase) encoded by neighboring genes may catalyze peptide bond formation. Similar enzymes are used in the biosynthesis of the phosphonopeptides rhizocticin (21) (ATP-grasp ligases) and dehydrophos (37) (GNAT), and a combination of both has been suggested to account for the peptide linkages in fosfazinomycin (38). Argolaphos has broad-spectrum antibacterial activity, with the highest efficacy against Salmonella typhimurium, Escherichia coli, and Staphylococcus aureus, and it is weakly inhibitory against Mycobacterium smegmatis (SI Appendix, Fig.…”
Section: Dereplication Of Phosphonate Biosynthetic Pathways and Produmentioning
confidence: 99%
“…Including the eight additional molecules we recently reported elsewhere (24,38,40,45) (SI Appendix, Fig. S4), this program has yielded 19 new phosphonate natural products to date.…”
Section: Pepmentioning
confidence: 99%
“…1, 2 At present, the mechanism of N-N bond formation is not understood. 3, 4 In recent years, the biosynthetic gene clusters have been reported for several such compounds, including valanimycin, 3, 5 kutzneride, 4, 6 and fosfazinomycin, 7 as well as molecules containing diazo groups such as kinamycin, 8, 9 lomaiviticin, 10, 11 and cremeomycin 12, 13 (Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, a recent study by van der Donk, Metcalf, and co-workers identified homologs of lom32–35 in a putative fosfazinomycin ( fzm ) biosynthetic gene cluster. 25 Fosfazinomycin contains a hydrazido linkage, and the presence of these lom genes in the fzm cluster provides further evidence for their involvement in N–N bond formation (Figure 3B). We also noted that fznP displays significant sequence homology to hypothetical protein lom29 (30% amino acid identity, 43% similarity).…”
Section: Resultsmentioning
confidence: 84%